2016
DOI: 10.1111/pan.12864
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on preemptive analgesia for acute postoperative pain management in children

Abstract: Preemptive analgesia using IV-PCA with fentanyl showed no significant advantages for postoperative analgesia after corrective osteotomy in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In a recent study, Song et al reported that for pediatric patients undergoing corrective osteotomy, preemptive analgesia using intravenous PCA with fentanyl did not significantly affect postoperative pain. 15 However, this study had two key limitations that may explain these negative results. First, they compared the effects of PCA when initiated either just before or after skin incision, conforming to the classic view of preemptive analgesia.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent study, Song et al reported that for pediatric patients undergoing corrective osteotomy, preemptive analgesia using intravenous PCA with fentanyl did not significantly affect postoperative pain. 15 However, this study had two key limitations that may explain these negative results. First, they compared the effects of PCA when initiated either just before or after skin incision, conforming to the classic view of preemptive analgesia.…”
Section: Discussionmentioning
confidence: 89%
“…Acute pain is extremely important to manage well in children, given poorly managed acute pain is a significant factor in the transition from acute to chronic pain and suboptimal pain management can lead to increased pain experience and decreased cooperation in subsequent medical visits . A common medical event involving acute pain is surgery and in fact, millions of children undergo surgery each year in the US and the majority experience significant pain postoperatively . Accordingly, WebTIPS (http://centeronstressandhealth.hs.uci.edu/research_periop.shtml) is an Internet‐based surgical preparation program for children and families that aims to reduce preoperative anxiety and postoperative pain .…”
Section: Mhealth Programs For Pediatric Painmentioning
confidence: 99%
“…,24 A common medical event involving acute pain is surgery and in fact, millions of children undergo surgery each year in the US and the majority experience significant pain postoperatively 4,[25][26][27]. Accordingly, WebTIPS (http://centeronstressandhealth.…”
mentioning
confidence: 99%
“…The patients were transferred to the post-anesthetic care unit (PACU) and stayed for at least 30 min for stabilization. We also checked the postoperative pain scale (FLACC scale) [18] and emergence delirium scale (PAED scale) [19] in the PACU.…”
Section: Study Protocolmentioning
confidence: 99%